Flexible Near‐Infrared Plastic Phototransistors with Conjugated Polymer Gate‐Sensing Layers. (3rd April 2018) - Han, Hyemi; Lee, Chulyeon; Kim, Hwajeong; Kim, Youngkyoo
Abstract: Flexible near‐infrared (NIR) light‐sensing detectors are strongly required in the fast‐growing flexible electronics era, because they can serve as a vision system like eyes in various innovative applications including humanoid robots. Recently, keen interest has been paid to organic phototransistors due to their unique signal amplification and active matrix driving features over organic photodiodes. However, conventional NIR‐sensing organic phototransistors suffer from the limited use of organic materials because the channel layers play a dual role in both charge transport and sensing so that organic semiconducting materials with reasonably high charge mobility can be applied only. Here, it is demonstrated that a conjugated polymer, poly[{2, 5‐bis‐(2‐ethylhexyl)‐3, 6‐bis‐(thien‐2‐yl)‐pyrrolo[3, 4‐c]pyrrole‐1, 4‐diyl}‐ co ‐{2, 2′‐(2, 1, 3‐benzothiadiazole)]‐5, 5′‐diyl}] (PEHTPPD‐BT), which exhibits no transistor performance as a channel layer, can stably detect a NIR light (up to 1000 nm) as a gate‐sensing layer (GSL) when it is placed between gate‐insulating layers and gate electrodes. The flexible array (10 × 10) detectors with the PEHTPPD‐BT GSLs could effectively sense NIR light without visible light interference by applying visible light cut films. Abstract : Organic phototransistors, of which gate‐sensing layers consist of a conjugated polymer (poly[{2, 5‐bis‐(2‐ethylhexyl)‐3, 6‐bis‐(thien‐2‐yl)‐pyrrolo[3, 4‐c]pyrrole‐1, 4‐diyl}‐ co ‐{2, 2′‐(2, 1, 3‐benzothiadiazole)]‐5, 5′‐diyl}]) that is unable to play as a channel layer for transistors, can stably detect near‐infrared light up to 1000 nm even in a flexible array structure. This new concept paves a bright way for next‐generation phototransistors with various cheap organic materials without any transistor (channel) performances.